pH-Responsive Nanophotosensitizer Boosting Antibacterial Photodynamic Therapy by Hydroxyl Radical Generation - Peilin Tian; Xianyue Bai; Jing Feng; Luyao Xu; Shihao Xu; Xiaoya Yu; Caiju Fan; Qian Su; Jiaxing Song; Cuixia Lu (Nanomaterials)
In this study, a pH-responsive nanophotosensitizer (MT@Ce6) was rationally developed by strategic integration of MIL-101 (Fe)-NH2 metal–organic framework with tannic acid (TA) and chlorin e6. This nanocomposite exhibits pH-responsive degradation in acidic microenvironments, facilitating Fe3+ release and subsequent reduction to Fe2+ that catalyzes Fenton reaction-mediated hydroxyl radical (•OH) generation. This cascade reaction shifts reactive oxygen species (ROS) predominance from transient singlet oxygen (1O2) to the long-range penetrative •OH, achieving robust biofilm disruption and over 90% eradication of methicillin-resistant Staphylococcus aureus (MRSA) under 660 nm irradiation. In vivo evaluations revealed accelerated wound healing with 95% wound closure within 7 days, while species-selective antibacterial studies demonstrated a 2.3-fold enhanced potency against Gram-positive bacteria due to their unique peptidoglycan-rich cell wall architecture. These findings collectively establish a microenvironment-adaptive nanoplatform for precision antimicrobial interventions, providing a translational strategy to address drug-resistant infections.